Generational perspectives on logo complexity: influencing luxury perception and purchase intention - Zhang, Yueran (Frontiers in Communication, 2025)
IntroductionThis study provides branding guidance for fashion brands in the new economic landscape by examining how brand identity complexity influences luxury perception and purchase intention, particularly focusing on generational differences between Generation Z and Generation X.MethodsTwo experimental studies using self-reported questionnaires were conducted. Study 1 applied linear regression analysis to investigate the relationship between logo complexity, luxury perception, and purchase intention. Study 2 used hierarchical regression analysis to examine the moderating effect of generational differences on these relationships.ResultsStudy 1 found that complex logos positively influenced purchase intention (B = 0.533, p < 0.001), with luxury perception partially mediating this effect (B = 0.179, p < 0.001). Study 2 revealed generational differences did not moderate the relationship between logo complexity and luxury perception but did significantly moderate the relationships between logo complexity and purchase intention, and between luxury perception and purchase intention (ΔR2 = 0.008, p < 0.01; ΔR2 = 0.007, p < 0.01).ConclusionThe findings suggest emerging brands should consider adopting complex logos to enhance perceived value. Conversely, established brands may benefit more from reinforcing brand consistency and using subtle luxury cues. While perceived luxury remains stable across generations, tailored communication strategies—such as emphasizing innovation for Generation Z and craftsmanship for Generation X—could optimize brand alignment across different consumer segments.